Case report: Successful medical management of adrenocortical carcinoma with metastasis in a Maltese dog - Park, Sin-Wook; Kim, Keon; Kim, Ock-Kyu; Ro, Woong-Bin; Lee, Chang-Min (Frontiers in Veterinary Science, 2023)
Adrenocortical carcinoma (ACC) with metastasis has a grave prognosis, and adrenalectomy is associated with a high perioperative mortality rate in dogs. A favorable outcome following trilostane treatment in patients with metastatic ACC confirmed by a decreased size of the adrenal tumor and metastatic lesions has not been reported in dogs.A 12-year-old neutered male Maltese dog was diagnosed with a right adrenal tumor and a hepatic mass. Adrenal-dependent hyperadrenocorticism (ADH) was diagnosed based on clinical signs and an adrenocorticotropic hormone stimulation test (ACTHST). In addition, tests for plasma metanephrine and normetanephrine ruled out a pheochromocytoma. Based on cytology and computed tomography, unresectable metastatic ACC was confirmed. The dog was managed with trilostane due to the presence of distant metastasis. Medical management improved the clinical signs and post-ACTHST cortisol concentrations. One year after the first presentation, the clinical signs and ACTHST test showed a favorable outcome. In addition, computed tomography revealed a decreased size of the right adrenal tumor and resolution of the hepatic mass.Trilostane could be considered as a treatment option for unresectable metastatic ACC. A decrease in tumor size following treatment with trilostane has not been reported in dogs. This case report is the first to demonstrate a favorable outcome of metastatic ACC following trilostane mono therapy for greater than one year.